Elevated lactate as a mortality factor in poly traumatised patients: A systematic review and meta-analysis - Iturregui Paucar, Cori Raquel (2023)
Introduction: According to global health estimates from the World Health Organization (WHO) injuries represent 8% of world deaths. There are systematic reviews that relate lactate and mortality in trauma patients but do not focus on multiple trauma patients. Objective: To determine if elevated lactate is a mortality factor in multiple trauma patients. Methodology: A systematic review and meta-analysis of observational studies were carried out. The search was carried out in 4 databases: PUBMED, Embase, Scopus, and Web of Science. Data were pooled using a random effects model and summary statistics were calculated using odds ratios (ORs) with their respective 95% confidence intervals (95% CI). Results: Nine studies were included (n=5302). A significant association was found between elevated admission lactate with mortality (OR: 1.80; 95% CI 1.11 to 2.91) and 72-hour mortality (OR: 1.24; 95% CI 1.02 to 1.50). No statistically significant association was found for the analysis of elevated admission lactate and 28-day mortality (OR: 1.24; 95% CI 1.02 to 1.50). Finally, elevated admission lactate is associated with mortality regardless of time (OR: 1.34; 95% CI 1.19 to 1.50). Conclusion: Elevated admission lactate is associated with mortality and 72-hour mortality in multiple trauma patients. No significant association was found between elevated admission lactate and 30-day mortality. Elevated intake of lactate is associated with mortality independent of time.